2015
DOI: 10.1130/g37013.1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent monsoonal forcing of Mediterranean Outflow Water dynamics during the late Pleistocene

Abstract: The mode and vigor of the global oceanic circulation critically depend on the salinity of (sub)surface water masses advected to the loci of deep-water formation. Within the Atlantic meridional overturning circulation (AMOC), an important supplier of high-salinity waters is the Mediterranean Outflow Water (MOW), discharging into the North Atlantic via the Strait of Gibraltar. Despite its importance for the North Atlantic salinity budget, the long-term dynamics of MOW production have remained poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 27 publications
15
95
1
Order By: Relevance
“…Additionally, a renewed tectonic activity from ~600 kyr to ~300 kyr [ Hernanndez‐Molina et al , ] could have caused a modification of the MOW pathway along the upper slope and a reduction in MOW flow strength resulting in a general fining of the sediment. Site U1386 is also closely located to the moat generated by the MOW [ Hernández‐Molina et al , ; Stow et al , ] making it most sensitive to variations in bottom current velocity as it represents the upper boundary layer of the MOW [ Bahr et al , ]. Nevertheless, the presence of at least short‐term, interglacial MOW variability can be traced in the grain size changes at Site U1386 during MIS 11, MIS 9, and MIS 7 (Figure a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a renewed tectonic activity from ~600 kyr to ~300 kyr [ Hernanndez‐Molina et al , ] could have caused a modification of the MOW pathway along the upper slope and a reduction in MOW flow strength resulting in a general fining of the sediment. Site U1386 is also closely located to the moat generated by the MOW [ Hernández‐Molina et al , ; Stow et al , ] making it most sensitive to variations in bottom current velocity as it represents the upper boundary layer of the MOW [ Bahr et al , ]. Nevertheless, the presence of at least short‐term, interglacial MOW variability can be traced in the grain size changes at Site U1386 during MIS 11, MIS 9, and MIS 7 (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…The MOW constitutes of warm and relatively saline water masses exiting the Mediterranean Sea through the Strait of Gibraltar [ Ambar and Howe , ; Bryden et al , ; Bryden and Stommel , ]. As such, the Gulf of Cadiz is hydrographically directly linked to changes in the Mediterranean Sea source region through the MOW [ Bahr et al , ; Jiménez‐Espejo et al , ; Kaboth et al , ; Voelker et al , ]. The saline water masses of the MOW are thought to be an important modulator of the North Atlantic salt budget at intermediate water levels and proposed to precondition Atlantic Meridional Overturning Circulation (AMOC) [ Voelker et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…We argue that the changes in the surface water masses potentially relate to an intensification in the intermediate not the deep-water branch of the overturning cell stimulated by the increased northward protrusion of MOW. Such a scenario has already been highlighted in Bahr et al (2015) for MIS 5 and Late Pleistocene climatic conditions. Hence, the Early Pleistocene MOW might have acted as a positive climatic feedback mechanism against the background of increasingly colder temperatures.…”
Section: Did Mow Contribute To the Early Pleistocene Climate Transition?mentioning
confidence: 95%
“…Several studies have demonstrated that the Mediterranean thermohaline circulation was highly sensitive to both the rapid climatic changes propagated into the basin from high latitudes of the Northern Hemisphere Moreno et al, 2002Moreno et al, , 2005Paterne et al, 1999;Martrat et al, 2004;Sierro et al, 2005;Frigola et al, 2007Frigola et al, , 2008 and orbitally forced modifications of the eastern Mediterranean freshwater budget mainly driven by monsoonal river runoff from the subtropics (Rohling et al, 2002Bahr et al, 2015). A link between the intensification of the Mediterranean Outflow Water (MOW) and the intensity of the Atlantic Meridional Overturning Circulation (AMOC) was proposed (Cacho et al, , 2001Bigg and Wadley, 2001;Sierro et al, 2005;Voelker et al, 2006) and recently supported by new geochemical data in sediments of the Gulf of Cádiz .…”
Section: Introductionmentioning
confidence: 99%